Degradation of de‐esterified pctin/homogalacturonan by the polygalacturonase GhNSP is necessary for pollen exine formation and male fertility in cotton. Issue 6 (18th February 2022) - Wu, Yuanlong; Li, Xiao; Li, Yanlong; Ma, Huanhuan; Chi, Huabin; Ma, Yizan; Yang, Jing; Xie, Sai; Zhang, Rui; Liu, Linying; Su, Xiaojun; Lv, Rongjie; et al.
Summary: The pollen wall exine provides a protective layer for the male gametophyte and is largely composed of sporopollenin, which comprises fatty acid derivatives and phenolics. However, the biochemical nature of the external exine is poorly understood. Here, we show that the male sterile line 1355A of cotton mutated in NO SPINE POLLEN ( GhNSP ) leads to defective exine formation. The GhNSP locus was identified through map‐based cloning and confirmed by genetic analysis (co‐segregation test and allele prediction using the CRISPR/Cas9 system). In situ hybridization showed that GhNSP is highly expressed in tapetum. GhNSP encodes a polygalacturonase protein homologous to AtQRT3, which suggests a function for polygalacturonase in pollen exine formation. These results indicate that GhNSP is functionally different from AtQRT3, the latter has the function of microspore separation. Biochemical analysis showed that the percentage of de‐esterified pectin was significantly increased in the 1355A anthers at developmental stage 8. Furthermore, immunofluorescence studies using antibodies to the de‐esterified and esterified homogalacturonan (JIM5 and JIM7) showed that the Ghnsp mutant exhibits abundant of de‐esterified homogalacturonan in the tapetum and exine, coupled with defective exine formation. The characterization of GhNSP provides new understanding of the role of polygalacturonase and de‐esterified homogalacturonan in pollen exine formation.